Shade Matching in Fixed Partial Denture Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Shade matching is a significant process in fixed dental prosthesis where the selection needs special attentionand systemic approach in covering all aspects. It is a fact that this approach is mainly used for achievingthe goals related to the morphological and optical acceptance within the community settings. A total of 960patients were taken and analysed for shade matching in fixed partial denture. The data collection is donefrom the dental archives of the patient management software system. The study is done under universitysetting. The results were analysed using SPSS software version 20 by IBM.T he result observed is that thereis a highly achieved shade match with positive correlation and significant values (p
Keywords: Aesthetics; Shade match; Shade selection.